Thank You to Our 2019 Reviewers. (13th March 2020) - Faccenna, Claudio; Becker, Thorsten; Behr, Whitney; Blichert‐Toft, Janne; Edmonds, Marie; Faul, Ulrich; Feinberg, Joshua; Long, Maureen; Lithgow‐Bertelloni, Carolina R.; Paytan, Adina; van der Beek, Peter; Williams, Branwen
Abstract : The publishing process relies on the work of volunteer reviewers, and evaluating the interdisciplinary papers published in G‐Cubed can be challenging. As Editors and Associate Editors, we would like to give our appreciation to all reviewers and would like to acknowledge them in this editorial. G‐Cubed published 326 manuscripts out of 650 submissions in 2019, thanks on the efforts of 860 dedicated reviewers. Their names are listed below, and in italics are those who provided three or more reviews. A big thank you from the G‐Cubed team! Key Point: The editors thank the 2019 peer reviewers